Rancang Bangun Sistem Informasi Recording Sekolah pada Sekolah Menengah Atas (Studi pada Sekolah Menengah Atas Negeri 105 Jakarta) - Septi Sulistio Ardoko; Buce Trias Hanggara; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
SMAN 105 in current state still minimize the use utilization of information system to carry out learning activity or administration. On that basis, research carried out at SMAN 105 Jakarta in order to develop school information recording system needed by SMAN 105 Jakarta. As of time of the writing, SMAN 105 Jakarta only have a website only for displaying general information of the school and is also configuration on the website limited by the direction of ministry of educational indonesia. The software development life cycle used to develop the sistem are based on waterfall. On the framework side, the sistem is based on codeigniter framework and using UML as a base to develop the diagram used to build the diagram like use case and such. For testing the software, blackbox testing were used to test functional and non functional requirement which gave valid result as test were rolled to test the system. User Acceptance Testing (UAT) used to the stakeholder gave a 100% acceptance result using Guttman scale which mean that the system is accepted by the stakeholder.